Academic Workload and Burnout as Predictors of Counseling Needs Among University Students - Habel Saud; Sally Putri Karisma; Almendo Rudolf Mofu (Universitas PGRI Yogyakarta, 2026)
University students frequently encounter significant psychological distress stemming from academic demands, yet the specific predictors of their need for professional counseling services remain underexplored, particularly in under-resourced higher education contexts such as Papua, Indonesia. This study aimed to examine whether academic workload and academic burnout jointly and partially predict students' counseling needs at the Faculty of Teacher Training and Education, Universitas Cenderawasih. A quantitative survey design was employed with a sample of 147 third-semester students selected through purposive sampling from 14 study programs. Data were collected using validated self-report instruments (Aiken's V = 0.952; α = 0.961) and analyzed using multiple linear regression. The regression model was significant, with both predictors jointly accounting for 24.9% of the variance in counseling needs (F = 24.038, p < .001, R² = 0.249). However, partial analysis revealed that only academic burnout emerged as a significant predictor (β = 0.467, p < .001), while academic workload was not statistically significant (β = 0.129, p = .078). Academic burnout, rather than workload per se, is the primary driver of students' counseling needs, suggesting that counseling interventions should prioritize burnout-specific strategies such as cognitive restructuring, stress management, and psychoeducation over workload reduction alone. These findings provide an empirical basis for designing targeted, evidence-based counseling services in higher education. Limitations include the cross-sectional design, reliance on self-report data, single-institution sampling, and a low response rate (14.7%), which may affect generalizability. Keywords: academic workload, burnout, counseling needs, higher education, university students